Regional Analysis and Strategy for Development of Coffee Commodities in Banyuwangi Regency - Firdaus, Ragel; Aji, Joni Murti Mulyo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The plantation subsector always has a strategic role for regional development, both national and regional. Banyuwangi Regency is one of the coffee centers in East Java, with an average area of coffee commodities in Banyuwangi Regency of 8,675 Ha with average productivity from 2018-2022 reaching 904.4 kg/ha. The development of coffee commodities in Banyuwangi Regency is still experiencing several obstacles in increasing productivity and management. In the basic economic sectoral planning model, economic sectors are divided into basic sectors and non-basic sectors. The basic sector can be the basis for decision making in strategic management of coffee commodity development. Base area analysis is carried out using Location Quotient (LQ) analysis, while localization analysis and specialization analysis are used to determine distribution characteristics. The coffee commodity development strategy is determined by the Analytical Hierarchy Process (AHP). There are 6 coffee commodity base regions or sub-districts in Banyuwangi Regency based on the average LQ from 2018-2022. The average value of the locality and specialization coefficients is less than one. The priority criteria in the coffee commodity development strategy are post-harvest farming criteria, while the alternative is the alternative of increasing the mechanization of product processing.